Peran Lembaga Pembiayaan Syariah dalam Mempercepat Pemulihan UMKM di Masa Pandemi - Nasution, Lokot Zein (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
Covid-19 pandemic has not only impacted the health sector, but also social, political, security, and especially the economic sector. Various empirical studies prove that the Covid-19 pandemic has significantly reduced market demand due to social activities and trade transactions. SMEs are one of the most powerful business actors, and a threat to business in the long term. The source of the problem is the low accessibility of financing, including the non-optimal use of sharia financing during the pandemic. how this can be done to find and explore Islamic financing institutions that can be done in the recovery of pandemic MSMEs. Based on a review of the study literature, it was found that Islamic financing has advantages in the form of the principle of risk sharing to overcome the vulnerability of SMEs businesses. Another advantage lies in sharia guidelines that are in accordance with democracy, and the application of the precautionary principle. In Islamic financing, there is no party who benefits above the loss of the other party, and there is no unilateral or repressive treatment to other parties. The advantage it has is that Islamic financing must be conditioned to suit business needs, equipped with an empowerment model as part of the SMEs financing scheme. For this reason, the government needs to encourage the Islamic finance ecosystem as a foundation in developing Islamic financing institutions for the recovery of SMEs during the pandemic.